2001
DOI: 10.2134/agronj2001.9351164x
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Repeated Trinexapac‐Ethyl Applications on Kentucky Bluegrass

Abstract: Pers.], and 'Tifway' bermudagrass [C. dactylon (L.) Pers. ϫ C. transvaalensis Burtt-Davy] (Johnson, 1992).Reducing turfgrass clipping production is often the goal of manag-Repeated monthly applications of TE to a mixed stand ers who recognize the need to save time, money, or landfill space. The objective of this study was to investigate the long-term implications of of colonial bentgrass (Agrostis tenuis Sibth.), highland repeated trinexapac-ethyl [4-(cyclopropyl-␣-hydroxy-methylene)-3, bentgrass (A. caste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 16 publications
8
46
1
Order By: Relevance
“…Our results indicated that three or more sequential TE applications resulted in more leaf TC. These data and other reports (Ervin and Zhang, 2007;Freddie et al, 2005;Lickfeldt et al, 2001) support the hypothesis that TC may be accumulated more during the period of TE inhibition in order to be used to fuel other sink tissues such as increased tillering, stem growth, or rooting.…”
Section: Total Carbohydrates (Tc)supporting
confidence: 86%
See 1 more Smart Citation
“…Our results indicated that three or more sequential TE applications resulted in more leaf TC. These data and other reports (Ervin and Zhang, 2007;Freddie et al, 2005;Lickfeldt et al, 2001) support the hypothesis that TC may be accumulated more during the period of TE inhibition in order to be used to fuel other sink tissues such as increased tillering, stem growth, or rooting.…”
Section: Total Carbohydrates (Tc)supporting
confidence: 86%
“…temperatures (Beasley, 2005;Fagerness et al, 2002;Lickfeldt et al, 2001) and reversely decreased TE efficacy at warmer temperature which was associated with an accelerated rate of TE metabolism in the former (Beasley, 2005).…”
Section: Canopy Heightmentioning
confidence: 99%
“…In contrast, high doses provide better results for longer periods, but with higher levels of injury. This imbalance between efficiency and injury can be solved with sequential applications involving welladjusted doses (Fagerness & Yelverton, 2000;Lickfeldt, et al, 2001, McCarty et al, 2004Waltz Jr. & Whitwell, 2005;Ervin & Zhang, 2007;McCullough et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…During all the years of research (2002)(2003)(2004), the growth of grass on plots treated with the regulator, compared to the control, was considerably slow, suppressed by trinexapac-ethyl. Lickfeldt et al (2000) showed that lawns treated with TE demonstrated better quality than lawns where TE had not been applied, regardless of the type of fertilizer used.…”
Section: Resultsmentioning
confidence: 98%